2013
DOI: 10.1371/journal.pone.0073552
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and Progesterone Exhibit Similar Patterns of Hepatic Gene Expression Regulation in the Bovine Model

Abstract: Female sex steroid hormones, estradiol-17β (E2-17β) and progesterone (P4) regulate reproductive function and gene expression in a broad range of tissues. Given the central role of the liver in regulating homeostasis including steroid hormone metabolism, we sought to understand how E2-17β and P4 interact to affect global gene expression in liver. Ovariectomized cows (n = 8) were randomly assigned to 4 treatment groups applied in a replicated Latin Square design: 1) No hormone supplementation, 2) E2-17β treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…These might explain why E2 and P4 have the same prevention effects on FA‐induced inhibitions in endothelial cell proliferation and migration. The overlapping actions of E2 and P4 were also demonstrated previously on the regulation of liver transcriptome …”
Section: Discussionsupporting
confidence: 71%
“…These might explain why E2 and P4 have the same prevention effects on FA‐induced inhibitions in endothelial cell proliferation and migration. The overlapping actions of E2 and P4 were also demonstrated previously on the regulation of liver transcriptome …”
Section: Discussionsupporting
confidence: 71%
“…Given the central role of the liver in the regulation of glucose homeostasis, we also assessed the effects of E 2 and P 4 on hepatic glucose metabolism. Although the opposing effects of E 2 and P 4 on oxidative stress processes have been reported in vitro 31 32 33 , a recent in vivo study using microarray analysis showed that E 2 , P 4 , and their co-treatment actually displayed similar patterns and networks of hepatic gene expression 34 . Consistent with the previous study, we found that E 2 and P 4 presented similar phenotypes and protein content profiles in regulating hepatic glucose metabolism.…”
Section: Discussionmentioning
confidence: 95%